Advances in Polymer Sciences and Technology Select Papers from APA 2017 (Materials Horizons: From Nature to Nanomaterials,, 2018)
This book presents select papers presented at the annual meeting of the Asian Polymer Association. The chapters in this volume document and report on a wide range of significant recent results for various applications, as well as scientific developments in the areas of polymer science and engineering. The chapters include original research from all areas of polymer science and technology with a focus on the manufacture, processing, analysis and application of long chain polymer molecules. This book will be of interest to researchers in academia and industry alike. .